Advances in pan‐European flood hazard mapping. Issue 13 (16th July 2013) - Alfieri, Lorenzo; Salamon, Peter; Bianchi, Alessandra; Neal, Jeffrey; Bates, Paul; Feyen, Luc
Abstract Flood hazard maps at trans‐national scale have potential for a large number of applications ranging from climate change studies, reinsurance products, aid to emergency operations for major flood crisis, among others. However, at continental scales, only few products are available, due to the difficulty of retrieving large consistent data sets. Moreover, these are produced at relatively coarse grid resolution, which limits their applications to qualitative assessments. At finer resolution, maps are often limited to country boundaries, due to limited data sharing at trans‐national level. The creation of a European flood hazard map would currently imply a collection of scattered regional maps, often lacking mutual consistency due to the variety of adopted approaches and quality of the underlying input data. In this work, we derive a pan‐European flood hazard map at 100 m resolution. The proposed approach is based on expanding a literature cascade model through a physically based approach. A combination of distributed hydrological and hydraulic models was set up for the European domain. Then, an observed meteorological data set is used to derive a long‐term streamflow simulation and subsequently coherent design flood hydrographs for a return period of 100 years along the pan‐European river network. Flood hydrographs are used to simulate areas at risk of flooding and output maps are merged into a pan‐European flood hazard map. The quality of this map is evaluated for selected areas in Germany and United Kingdom against national/regional hazard maps. Despite inherent limitations and model resolution issues, simulated maps are in good agreement with reference maps (hit rate between 59% and 78%, critical success index between 43% and 65%), suggesting strong potential for a number of applications at the European scale. Copyright © 2013 John Wiley & Sons, Ltd.